The Probiotic Identity Card: A Novel “Probiogenomics” Approach to Investigate Probiotic Supplements - Lugli, Gabriele Andrea; Longhi, Giulia; Alessandri, Giulia; Mancabelli, Leonardo; Tarracchini, Chiara; Fontana, Federico; Turroni, Francesca; Milani, Christian; Di Pierro, Francesco; van Sinderen, Douwe; Ventura, Marco (Frontiers in Microbiology, 2022)
Probiotic bacteria are widely administered as dietary supplements and incorporated as active ingredients in a variety of functional foods due to their purported health-promoting features. Currently available probiotic products may have issues with regards to their formulation, such as insufficient levels of viable probiotic bacteria, complete lack of probiotic strains that are stated to be present in the product, and the presence of microbial contaminants. To avoid the distribution of such unsuitable or misleading products, we propose here a novel approach named Probiotic Identity Card (PIC), involving a combination of shotgun metagenomic sequencing and bacterial cell enumeration by flow cytometry. PIC was tested on 12 commercial probiotic supplements revealing several inconsistencies in the formulation of five such products based on their stated microbial composition and viability.